PENERAPAN PEMBELAJARAN INKUIRI PADA MATERI KENAMPAKAN PERMUKAAN BUMI UNTUK MENINGKATKAN HASIL BELAJAR SISWA SD KELAS III (Penelitian Tindakan Kelas pada Materi Kenampakan Permukaan Bumi di Kelas III SDN Sindangraja Kecmatan Sumedang Utara Kabupaten Sumedang) - Tresnayani, Amelyandini (2017)
Based on preliminary observations conducted on grade 3rd students of Sindangraja state primary school obtained a problem, that is on the learning process of many students who noisy and not concentrated in learning. In conveying the material, teachers tend to use conventional approach so that students are less motivated in following the learning as the solution of the problem, used inquiry model of learning. The purpose of this study is to test the inquiry model learning of students on the material surface appearance of the earth watersin class 3rd in the inquiry model of a students centered learning to find their own material to be learned, so the inquiry learning model makes the lesson become meaningful. Research with this inquiry model include planning, implementation, student learning outcomes, and student activities. The method used in this study is a classroom action research with reference to the spiral model of Kemmis and Taggart. The subjek of this research at grade 3rd in Sindangraja state primary school as many as 24 students. This research is done 3 cycles because Taggart of the research is reached in cycle 3. As fo the target that is determined 85% for students learning result, while for 90% for student activity and teacher performance. The data obtained in the research process, that is the teacher performance earned 77% in cycle 1, 91% in cycle 2, and 95% in cycle 3. While the students activity at cyle 1 65%, on cycle 2 80%, and on cycle 3 90%. Learning outcomes at cycle 1 48%, on cycle 2 79%, and on cycle 3 87,5%. Based on the data obtained in the research process, there has been an increase in students learning outcomes. It proves that the application of inquiry learning model can improve student learning outcomes.